Medical adverse events in elderly hospitalized patients: A prospective study - Szlejf, Claudia (Hospital das Clínicas da Faculdade de Medicina da Universidade de São Paulo, 2012)
OBJECTIVES: To determine the frequency of medical adverse events in elderly patients admitted to an acute care geriatric unit, the predictive factors of occurrence, and the correlation between adverse events and hospital mortality rates. METHODS: This prospective study included 171 admissions of patients aged 60 years and older in the acute care geriatric unit in a teaching hospital in Brazil between 2007 and 2008. The following variables were assessed at admission: the patient age, gender, number of prescription drugs, geriatric syndromes (e.g., immobility, postural instability, dementia, depression, delirium, and incontinence), comorbidities, functional status (evaluated with the Katz Index of Independence in Activities of Daily Living), and severity of illness (evaluated with the Simplified Acute Physiology Score II). The incidence of delirium, infection, mortality, and the prescription of potentially inappropriate medications (based on the Beers criteria) were assessed during hospitalization. An observer who was uninvolved in patient care reported the adverse events. RESULTS: The mean age of the sample was 78.12 years. A total of 187 medical adverse events occurred in 94 admissions (55%). The predictors of medical adverse events were undetermined. Compared with the patients with no adverse events, the patients with medical adverse events had a significantly longer hospital stay (21.41±15.08 days versus 10.91±7.21 days) and a higher mortality rate (39 deaths [41.5%] versus 17 deaths [22.1%]). Mortality was significantly predicted by the Simplified Acute Physiology Score II score (odds ratio [OR] = 1.13, confidence interval [CI] 95%, 1.07 to 1.20), the Katz score (OR = 1.47, CI 95%, 1.18 to 1.83), and medical adverse events (OR = 3.59, CI 95%, 1.55 to 8.30). CONCLUSION: Medical adverse events should be monitored in every elderly hospitalized patient because there is no risk profile for susceptible patients, and the consequences of adverse events are serious, sometimes leading to longer hospital stays or even death.